Transcriptome-based phylogenomic analysis reveals evidence of ancient hybridization events in the Mepraia genus (Hemiptera: Reduviidae: Triatominae) - Belintani, Tiago (2023)
Introduction: The Mepraia genus is composed of three endemic species in Chile, namely Mepraia spinolai, Mepraia gajardoi, and Mepraia parapatrica, all capable of transmitting the causative agent of Chagas disease. Although species divergence within this genus is supported by morphological, molecular, and geological evidence, it has never been validated by genome-wide data. Methods: In this sense, a pioneering phylogenomic study was conducted using transcriptome data of the three species, aiming to infer robust phylogenies and evaluate the impact of interspecific gene flow on the evolution of these insects. Our transcriptomes were used to robustly infer the phylogenetic relationships, employing multi-species coalescent and supermatrix approaches, as well as to investigate the occurrence of introgression. Results and discussion: The inferred phylogenies support the monophyly of the three described taxa and infer divergence times, although gene trees display high levels of discordance. Our results indicate widespread introgression among Mepraia lineages. Thus, our results support that Mepraia diversification occurred in a short period resulting in reticulate phylogenies and low genetic diversity. Additionally, we obtained evidence of introgression suggesting that ancient hybridization has had a major role in the evolution of the three Mepraia species.